Hubungan Budaya Organisasi dan Kepuasan Pegawai terhadap Produktivitas Kerja pada Badan Pusat Statistik Kab. Sukoharjo - Destifa Umari Ramadhanti; Taufiq Muftiyanto; Khabib Alia Akhmad (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
The study aims to determine the relationship between organizational culture and employee satisfaction on work productivity at the Central Bureau of Statistics Sukoharjo Regency. The research method used in this research is quantitative research method. Sampling using saturated samples with a total of 50 respondents. The data source used is primary data and data collection by distributing questionnaires directly. The analysis technique used is IBM SPSS version 25.0. The results in this study indicate that: (1) Organizational culture has a positive and significant effect on work productivity (2) Employee satisfaction has a positive and significant effect on productivity (3) Organizational culture and employee satisfaction have a positive and significant effect on work productivity.